Kikuchi-Fujimoto disease followed by systemic lupus erythematosus in a male child: A diagnostic challenge - Sruthi Kodali; Geeta Kiran Arakkal; Sandeep Kodali; Kolluri Siva Bala Vaishnavi (Wolters Kluwer Medknow Publications, 2024)
Kikuchi-Fujimoto disease (KFD) is a benign self-limiting condition characterized by fever and necrotizing lymphadenitis commonly reported in adults, especially females, and rarely in males and children. The disease can be mistaken for lymphoma or systemic lupus erythematosus (SLE) clinically and histologically. KFD may be associated with SLE. Recurrences of KFD are common and hemophagocytic lymphohistiocytosis is the most common complication. Herein, we report the case of KFD in a 5-year-old boy who presented with fever and cervical lymphadenopathy following which he developed SLE. The diagnosis was confirmed by lymph node biopsy and antinuclear antibodies profile. His condition met 7 out of 17 systemic lupus international collaborating clinics (SLICC) criteria for SLE.